The Use of Boosters in Written and Spoken Discourses by Indonesian ELT Students - Risda Asfina; Ririn Ovilia; Rindilla Antika (Universitas Negeri Padang, 2023)
This study aimed to delineate the use of by Indonesian English Language Teaching (ELT) graduate students boosters in written and spoken discourses. This study was a descriptive qualitative study involving 20 participants. The data were collected from the graduate students’ thesis background and their presentations in thesis proposal seminar. To calculate the frequency of boosters, corpus-based approach using a concordance software, i.e. AntConc (3.4.4) was used. The use of boosters was classified according to boosters taxonomy adapted from Hinkel (2005) and Hyland (2005). This study discovered that the patterns of the use of boosters in both discourses were alike: E–P–A. Second, more boosters were more applied in spoken discourse. Based on the total number of booster variant in taxonomy, roughly 65% was applied in both discourses. Therefore, discourse modes, written and spoken, can influence the use of boosters in academic discourse.